Cost effectiveness of home ultraviolet B phototherapy for psoriasis: economic evaluation of a randomised controlled trial (PLUTO study). (20th April 2010) - Koek, Mayke B G; Sigurdsson, Vigfús; van Weelden, Huib; Steegmans, Paul H A; Bruijnzeel-Koomen, Carla A F M; Buskens, Erik
Abstract : Objective To assess the costs and cost effectiveness of phototherapy with ultraviolet B light provided at home compared with outpatient ultraviolet B phototherapy for psoriasis. Design Cost utility, cost effectiveness, and cost minimisation analyses performed alongside a pragmatic randomised clinical trial (the PLUTO study) at the end of phototherapy (mean 17.6 weeks) and at one year after the end of phototherapy (mean 68.4 weeks). Setting Secondary care, provided by a dermatologist in the Netherlands. Participants 196 adults with psoriasis who were clinically eligible for narrowband (TL-01) ultraviolet B phototherapy were recruited from the dermatology departments of 14 hospitals and were followed until the end of phototherapy. From the end of phototherapy onwards, follow-up was continued for an unselected, consecutive group of 105 patients for one year after end of phototherapy. Interventions Ultraviolet B phototherapy provided at home (intervention) and conventional outpatient ultraviolet B phototherapy (control) in a setting reflecting routine practice in the Netherlands. Both treatments used narrowband ultraviolet B lamps (TL-01). Main outcome measures Total costs to society, quality adjusted life years (QALYs) as calculated using utilities measured by the EQ-5D questionnaire, and the number of days with a relevant treatment effect (≥50% improvement of the baseline self administered psoriasis area and severity index (SAPASI)). Results Home phototherapy is at least as effective and safe as outpatient phototherapy, therefore allowing cost minimisation analyses (simply comparing costs). The average total costs by the end of phototherapy were €800 for home treatment and €752 for outpatient treatment, showing an incremental cost per patient of €48 (95% CI €−77 to €174). The average total costs by one year after the end of phototherapy were €1272 and €1148 respectively (difference €124, 95% CI €−155 to €403). Cost utility analyses revealed that patients experienced equal health benefits—that is, a gain of 0.296 versus 0.291 QALY (home v outpatient) by the end of phototherapy (difference 0.0052, −0.0244 to 0.0348) and 1.153 versus 1.126 QALY by one year after the end of phototherapy (difference 0.0267, −0.024 to 0.078). Incremental costs per QALY gained were €9276 and €4646 respectively, both amounts well below the normally accepted standard of €20 000 per QALY. Cost effectiveness analyses indicated that the mean number of days with a relevant treatment effect was 42.4 versus 55.3 by the end of phototherapy (difference −12.9, −23.4 to −2.4). By one year after the end of phototherapy the number of days with a relevant treatment effect were 216.5 and 210.4 respectively (6.1, −41.1 to 53.2), yielding an incremental cost of €20 per additional day with a relevant treatment effect. Conclusions Home ultraviolet B phototherapy for psoriasis is not more expensive than phototherapy in an outpatient setting and proved to be cost effective. As both treatments are at least equally effective and patients express a preference for home treatment, the authors conclude that home phototherapy should be the primary treatment option for patients who are eligible for phototherapy with ultraviolet B light. Trial registration Current Controlled Trials ISRCTN83025173 and Clinicaltrials.gov NCT00150930